Effects of policies on patenting in wind power technologies - Joachim Schleich; Rainer Walz; Mario Ragwitz (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2016)
This paper explores factors driving innovation in wind power technologies in OECD countries by employing count data panel econometrics. Transnational patent data in wind power technologies serve as the indicator for innovation. In addition to classical supply side policies, the set of explanatory variables also reflects insights from the systems of innovation and policy analysis literature. The findings suggest that patenting is positively related to public R&D in wind power (reflecting supply side regulation), to the stock of wind capacity (learning effects), to the number of patents per capita (innovation capacity), to the share of Green party voters (legitimacy of technology), to targets for electricity from renewable energy sources, to the stability of the regulatory framework, and also to power prices (profitability). Feed-in-tariffs, which have been the predominant support mechanism for electricity from renewables, are not found to be positively related to patenting activity - unless they are implemented within a stable regulatory framework. These findings are robust to alternative model specifications and distributional assumptions.
urn:nbn:de:0011-n-3891671
Keywords: 330; innovation; supply-side regulation; demand-side regulation; wind power; patent analysis; count data econometrics